13.6k views
2 votes
Help!! YEEEEEEEEEEEEEEEEEET

Help!! YEEEEEEEEEEEEEEEEEET-example-1

1 Answer

3 votes

Answer:

Explanation:

Degree of quadratic equation is 2

So, y = (x + 2)² - 6 ; y = x² - 4x + 2 & y = -(x -2)² + 5 are quadratic equation

(a + b)² = a² + 2ab + b²

y = (x + 2)² - 6

y = x² + 2*x*2 + 2² -6

y= x² + 4x + 4 -6

y= x² + 4x - 2

Degree = 2

y = -(x - 2)² + 5

y = -[ x² - 2*x*2 + 2²] + 5

y = -[x² - 4x + 4)+5

y = -x² + 4x - 4 + 5

y = -x² + 4x + 1

Degree = 2

User Asken
by
5.3k points